Strategi Badan Narkotika Nasional Kabupaten Pulau Morotai dalam Melakukan Penangganan dan Pemberantasan Narkoba Didaerah Perbatasan - Tawaja Ramzia Djangoan; Idhan Dominggus (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the Strategy of the National Narcotics Agency of Morotai Island Regency in Efforts to Handle and Eradication of Drugs in 2019 in border areas, using qualitative descriptive research. The method of collecting data is through interviews with each informant selected by the researcher as primary data, observation and documentation as supporting data for the implementation of the research. After the data is collected, the next step is data analysis with the stages of reduction, presentation of data and drawing conclusions. The results showed that the Morotai Island BNNK Strategy in handling and eradicating drugs by initiating a number of plans starting from Advocacy, Urine Testing, Counseling, Dissemination, Mapping of vulnerable areas, and Empowerment. However, this strategy is considered less than optimal, due to the limited facilities to support the handling and eradication of drugs, namely resources and finance. This is quite reasonable, considering that the Morotai Island BNNK Morotai BNNK is still 5 years old, and in that period of time 3 times the leadership changes. and the lack of public awareness to be actively involved in reporting drug abuse cases that occur in their environment. From this research, the researcher recommends that there is a need for action by involving all elements of the Morotai Island Regency community. In addition, it is necessary to increase the work support facilities of the Morotai Island BNKK, which is marked by the addition of employee personnel (resources) both in terms of quality and quantity, strengthening the position of cross-institutional communication. and strengthen socialization for elements of society, government and students.